The Correlation Between Collagen Types and Ultrasound Feature Score in Evaluating the Vulnerability of Carotid Artery Plaque - Han, Ruijun; Yan, Yanhong; Ding, Yafang; Huang, Yabo; Zhou, Peng; Hui, Pinjing (Frontiers in Cardiovascular Medicine, 2021)
Objectives Investigate whether ultrasound score has clinical value in identifying carotid artery vulnerable plaque and the impacts of collagen distribution to the plaques stability. Materials and Methods Standard carotid artery ultrasound examinations were performed in 51 patients with carotid artery plaques before carotid endarterectomy. Hematoxylin-eosin staining and Sirius red-picric acid staining of plaque sections were performed to analyze pathological features and collagen distribution. All plaques were classified into vulnerable and stable group by pathological features. Ultrasound scores, cap thickness and ratios of different collagen were recorded and analyzed between 2 groups and different parts of plaques. Results Ultrasound scores of vulnerable group were higher than stable group (4.35±1.23 vs. 2.09±1.04, P= .001). AUC was 0.894 (best cut-off point 3) in differentiating vulnerable and stable plaque. Compared with stable group, the fibrous caps of vulnerable group were thinner (P=0.012); the area ratios of collagen type I to all collagen in vulnerable group were lower (P=0.033); however, the area ratios of collagen type IV to all collagen were higher (P=0.026). Compared with downstream shoulders, the ultrasound scores of plaque’s upstream shoulders were higher (P=0.001), the fibrous caps of upstream shoulders were thinner (P=0.001), and the area ratios of collagen type I to all collagen were lower (P=0.022). Conclusions Ultrasound score could have clinical value in identifying vulnerable carotid artery plaque and the collagen distribution could impact the stability of plaques, especially collagen type I and type IV. The results also prompted the upstream shoulders were more vulnerable than the downstream shoulders.